Organic spices in India: Potential, progress and pathway forward - Srinivasan, V; Thankamani, CK; Lijo Thomas; Praveena, R; M Shamsudheen; Dinesh, R (Indian Horticulture, 2025)
India holds immense potential in organic spice cultivation, driven by rising global demand for safe, eco-friendly produce. Organic farming excludes synthetic inputs, relying on sustainable practices to enhance soil health, biodiversity, and crop resilience. India leads with 1.4 million certified organic producers and 95,087 tonnes of organic spices produced in 2022–23, showcasing a 215% growth since 2014–15. Key spice-producing states include Madhya Pradesh, Kerala, and Sikkim. Research advancements at ICAR-IISR have led to the development of integrated organic management practices, disease-resistant varieties, and eco-friendly pest control measures. However, the sector faces challenges such as limited domestic market penetration, certification complexities, dependency on export markets, and inadequate traceability. This paper examines the current progress, production technologies, trade patterns, and challenges in India’s organic spice sector, proposing strategic pathways to enhance productivity, market access, and policy support to ensure sustainable development and global competitiveness in organic spice value chains.